Ecosystem services in cassava intercropping: a global synthetic review - Delaquis, Erik; Haan, Stef de; Wyckhuys, Kris A.G. (International Center for Tropical Agriculture, 2019)
Intensification and extensification of agriculture are eroding the integrity of tropical ecosystems. As global land comes under increasing anthropogenic management, considering the impacts of management practices on ecosystem services (ES) is essential. Cassava (Manihot esculenta Crantz) cultivation has expanded dramatically in the tropics, currently representing over 25 million hectares managed by millions of smallholders (Fig. 1). Diversification is often cited as a strategy for augmenting the functioning of ES in agricultural landscapes (Brooker et al., 2015; Kremen & Miles, 2012). Despite this, attempts to comprehensively evaluate diversification practices in cassava from an ES perspective remain rare. We conducted a systematic literature review of intercropping in cassava cultivation systems, and employed the concept of ES bundles to evaluate the impacts of diversification on a key set of ES.